Basic Aspects of Children’s Speech Training for School by Using Activity and Personality Approach - Kovshar, Olena (2020)
The research is devoted to the problem of speech training of preschool children before they begin studying at school. The terms “speech training for school”, “general speech training”, “special speech training” have been clarified. The essence and structure of the phenomenon of “communication and speech competence” are revealed, the criteria, indicators and levels of communication and speech competence are described. The experimental method of speech training for school by using activity and personality approach is researched. The speech readiness for learning is highlighted as a main condition for entry into the learning environment and a further successful learning start. The analysis of researches of modern scientists devoted to the phenomenon of “children’s speech training for school” (A. Bohush, M. Vashulenko, L. Kalmykova, N. Shylina) is conducted. It is revealed that the result of speech training is the formation of speech and communication competence of preschool age children. The criteria of speech and communication competence were phonetic, lexical, grammatical, diamonological competence with relevant indicators. Formation of speech and communication competence in the process of speech training by means of activity and personality approach involves the introduction of a specially developed program of speech training of older preschoolers before they get into studying at school: communication and speech situations, play-based speech exercises, variative dialogues. The results of the research confirmed the effectiveness of the proposed program for the formation of communication and speech competence in the process of speech training of older preschoolers before their studying at school.